You don't love your mother just because she feeds you : amaXhosa and woodlands in the Peddie district, Eastern Cape - McAlister, Gareth (Rhodes University, Faculty of Humanities, Department of Anthropology, 2013)
This thesis will discuss how the application of place theory might provide insight into how a selection of Xhosa-speaking people in a rural village (Ntloko), in the former Ciskei of the Eastern Cape, interact with and establish relationships with the local indigenous thicket forest (ihlathi). I am concerned with how these influence residents' perceptions and attitudes (relational epistemologies) towards this resource, and how these may (or may not) translate into conservation practices. I am also interested in how socio-political and economic changes have altered these people/place relations (including gender) and their corresponding cultural perceptions. It is argued that the local thicket forest's significance and importance moves beyond the economic and utilitarian value of its natural resources. The thicket plays an important part in local identity construction, due to both its socio-cultural significance and its role in local livelihoods. People form meaningful attachments and relationships (relational epistemologies ) with the thicket as a place, through their interactions with it. While this may or may not result in actions and attitudes in-line with the conservation agenda, it is shown that this relationship is necessary for a local concern and stake in the natural environment. Those who have no or minimal interaction, such as many of the young women of Ntloko, have no opportunity to forge a relationship with it. Ihlathi may be known through narrative, but not personal experience, and as such no significant attachments can be formed, and thus concern for its conservation status is irrelevant. It is clear that if you remove people from an environment, you remove the stake they hold in the environment in question, thereby disrupting the relationship, and alienating people from nature. While a relational epistemology may not equate to conservation practices, it does imply a stake or concern in the environment, and as such, may provide an opportunity for conservationists to work with local communities. Resistance to conservation and development projects that aim to exclude local interaction, and therefore relationships, with the environment, will always be strong when local identities are intricately tied to the places and experiences that form them. Threatening that relationship threatens local identities and the attachments that orient them.
Keywords: Xhosa (African people) -- Social life and customs; Forest ecology -- South Africa -- Eastern Cape; Forest conservation -- South Africa -- Eastern Cape; Social change -- South Africa -- Eastern Cape